The Tears of Odysseus: Brandstaetter’s Revisiting of the Ancient Homeric Tradition - Wesołowska, Elżbieta (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2018)
The paper focuses on the connections between Homeric poems, mainly Odyssey and the Polish drama Odysseus Crying by the Polish playwright Roman Brandstaetter, especially in the light of the motif of weeping and crying.